2018
DOI: 10.1080/21681163.2018.1537860
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of anatomical landmark selection for rib cage 3D reconstruction from biplanar radiography

Abstract: Methods to reconstruct anatomical structures in 3D are gaining interest in medicine because they give access to quantitative information on the patient's geometry. However, these methods are user-dependent and require a trained operator, which is time consuming and a source of error and unreliability. The aim of this work was to validate a novel method of landmark selection to perform the 3D reconstruction of the rib cage from biplanar calibrated radiographies. The method uses digital painting for digitization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…This is the most adopted position in radiological examination of scoliosis because the arms do not hide the spine neither in frontal radiographs nor in lateral ones, and the ribcage remains fairly visible in both views. Indeed, for a three-dimensional assessment of scoliosis, biplanar radiographs are acquired when possible, since they allow 3D reconstruction of the bony structures [21,22]. It is possible that feeding radiographs with patients in different position (such as in lateral bending [23]) could alter the results.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most adopted position in radiological examination of scoliosis because the arms do not hide the spine neither in frontal radiographs nor in lateral ones, and the ribcage remains fairly visible in both views. Indeed, for a three-dimensional assessment of scoliosis, biplanar radiographs are acquired when possible, since they allow 3D reconstruction of the bony structures [21,22]. It is possible that feeding radiographs with patients in different position (such as in lateral bending [23]) could alter the results.…”
Section: Discussionmentioning
confidence: 99%
“…The spine (T1-L5), ribcage and pelvis of each patient was reconstructed in 3 D with previously validated methods (Humbert et al 2009;Ghostine et al 2017;Vergari et al 2020), ; both before and in-brace (Figure 1). This reconstruction allowed automatic calculation of 3 D geometrical spinopelvic parameters, but it also provided 3 D models of all vertebrae, pelvis and rib cage, that were used to build a subject-specific finite element model of the trunk (Figure 1).…”
Section: Subject-specific Finite Element Modelmentioning
confidence: 99%
“…Patient balance was predicted through the analysis of balance compensation mechanisms between prebrace and in brace geometrical parameters (Vergari et al 2020). It was observed that the variation induced by the brace on the sagittal and axial orientation of T1 vertebra and on the sagittal orientation of the pelvis (i.e., pelvic tilt) could be predicted from pre-brace values (Figure 2).…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development and diffusion of biplanar stereoradiography gave access to high-quality radiographs without distortion while being 8e10 times less irradiating than conventional radiographs and 800 times less than computed tomography. 3D reconstruction methods have been developed, which can provide quantitative assessment of the trunk in the standing position [16][17][18][19]. Nevertheless, these methods were validated for adolescent idiopathic scoliosis patients as young as 10 years.…”
Section: Introductionmentioning
confidence: 99%